Obratnyi adres . Obratnyi adres . Return Address . Обратный адрес - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Social insecurity of the Russian population; segment on the rule of law and the mechanisms of human rights protection. Contributors: Dolgov, Georgii (Anchor) Социальная незащищенность населения России; сюжет о правовом государство и механизмы защиты прав. Создатели: Долгов, Георгий (Ведущий/Ведущая)